Peranan Protein Hewani dan Nabati dalam Mencegah Stunting pada Anak Usia Dini dan Ibu Hamil dengan Inovasi Pemberian Makanan Bergizi dari Nugget Daun Kelor di Kelurahan Cikerai Kecamatan Cibeber Kota Cilegon - Ayuri Shantika Sari; Surachman Surachman; Sumyati Sumyati; Redhian Putra; Desi Kusumawati (STIKes Ibnu Sina Ajibarang, 2024)
Stunting is another term for poor nutrition. Many studies have been conducted based on nutritious foods that are abundantly available in the home environment, one of which is Moringa leaves. The aim of Community Service (PKM) in the Health sector is because there are cases of stunting in the Cikerai Village, Cibeber District, Cilegon City. This research method was carried out through socialization and health education regarding nutritious foods to prevent stunting. The expected result is that stunting participants, sub-district/village officials, and health workers can support the acceleration of stunting reduction by preventing it through nutritious food from moringa leaves made into nuggets so that stunted children and pregnant women will receive intake from food innovations.